PENERAPAN PSAP 02 LAPORAN REALISASI ANGGARAN BERBASIS KAS PADA SEKRETARIAT DPRD KABUPATEN NIAS UTARA - Dedi Irawan Zebua; Jeliswan Berkat Iman Jaya Gea; Apriman Hura; Kurniawan Sarototonafo Zai, (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Assessing the financial performance of local governments can be done by looking at their performance, one of which is through the Budget Realization Report. . In this study, the researchers took the research locus at the Secretariat of the DPRD of North Nias Regency, which is the body that carries out the function of supporting local government finances. The main tasks of the North Nias DPRD Secretariat are to carry out secretarial administration, financial administration, support the implementation of the duties and functions of the Regional People's Representative Council and provide and coordinate the experts needed by the Regional House of Representatives in accordance with the regional financial capacity. The type of research used in this research is descriptive qualitative. The sampling technique in this study was purposive sampling. The sample in this study is the 2022 Budget Realization Report for the DPRD Secretariat of North Nias Regency.